GOVERNMENT EXPENDITURE AND POVERTY - Sri Isnowati; Gregorius N. Masdjojo; Rokh Eddy Prabowo (Universitas Tidar, 2023)
Poverty is a problem in developing countries. Poverty alleviation requires comprehensive and integrated handling, because this problem is multysectoral and multidimensional. This study aimed to analyze the effect of government education, health, and infrastructure expenditures on poverty in Central Java Province, Indonesia. The data in this study was the pooling data from 35 districts/cities in Central Java Province from 2018 to 2020. The data analysis method in this study is multiple regression analysis with panel data. The results of the analysis show that the regression coefficient for the variable government spending on education was negative. Health expenditure has a negative effect on poverty levels. Public work expenditure has a negative effect on poverty levels in Central Java Province, Indonesia. This policy implies that the role of local governments is very large in reducing poverty in Central Java, so a larger budget is needed to reduce poverty in Province of Central Java.